Poetry portfolio : Things I’ll never say and Mini-dissertation : The fragmented self : female identity in personal poetry, with particular reference to selected poems by Anne Sexton, Antjie Krog and Finuala Dowling - Medalie, David (University of Pretoria, 2013)
Dissertation (MA)--University of Pretoria, 2010.